Development of an electromagnetic vibrational energy harvesting system - Nizam, Rafquat; Ehsan, Md. Labib; Khan, Aurin; Khan, Raiyan (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.